Grain crops and forage yield resulting from the use of phosphates in integrated production system - Galetto, Shivelly; Fonseca, Adriel; Harkatin, Silvano; Reifur, Hendrik; Carvalho, Igor (Revista Ciência Agronômica, 2014)
The aim of this study was to assess the effects of the sources and levels of surface-applied (broadcast) phosphorus (P) when sowing the winter annual forages on phosphorus accumulation and yields of maize, soybean, black oat and annual ryegrass crops in a crop-livestock integration system over three years. The experiment was established in April 2009, in the municipality of Castro, Parana, Brazil. The treatments consisted of the broadcast application when sowing the winter forages of four doses (0, 60, 120 and 180 kg ha-1 year-1) of total P2O5 as triple superphosphate (TSP), rock phosphate (RP-Arad) and magnesium termophosphate (MTP). The dry matter yields of black oat (2009 and 2011), annual ryegrass (2010), maize (2009/10 and 2011/12) and soybean (2010/11) and the accumulation of P in these crops were assessed. TSP provided the highest yield of total dry matter (TDM) and P accumulation only for black oat in the first year of cultivation. In the second year, MTP resulted in higher P accumulation than occurred with the other P sources in annual ryegrass and soybean, and both MTP and TSP provided higher P accumulation and grain export. In the third year, MTP provided a higher TDM yield and P accumulation for both the black oat and maize crops, resulting in the greatest residual effect over time.